Early career psychiatrist’s attitude toward medicinal and recreational cannabis legalization in India; findings from an online survey. - Arya, Sidharth; Ghosh, Abhishek; Kazhungil, Firoz (Journal of Substance Use, 2023)
Background: The past two decades have seen significant debate around cannabis legalization globally, including in India. Since there is no data on professionals’ attitudes toward cannabis legalization; we aimed to assess early-career psychiatrists (ECP) views on cannabis legalization. Methods: An online survey consisting of questions regarding personal and socio-demographic details, attitudes toward legalization of medicinal cannabis and recreational cannabis, and potential indications of medicinal cannabis use was distributed to ECPs. Data from 105 respondents were analyzed using descriptive statistics, chi-square test, and t-test. Results: More respondents agreed with the legalization of medical cannabis (55%) as compared to recreational cannabis (23%). More than 80% ECPs considered cannabis to be associated with psychosis and adverse mental health outcomes; however, those in favor of legalization considered cannabis to be less harmful. ECP with past cannabis use was more likely to have a permissive attitude toward the legalization of recreational cannabis (χ2 =6.79, p < .05) but not for medicinal cannabis use (χ² =1.96, p > .05). Conclusion: ECP in India are open to the idea of legalizing cannabis for medicinal purposes but not for recreational purposes.